Handbook of less-common nanostructures - Charisov, Boris Il'dusovič; Kharissova, Oxana Vasilievna; Ortiz Méndez, Ubaldo (CRC Press, 2012)
"As nanotechnology has developed over the last two decades, some nanostructures, such as nanotubes, nanowires, and nanoparticles, have become very well known. However, recent research has led to the discovery of other, less common nanoforms, which often serve as building blocks for more complex structures. This book covers these structures and outlines their potential use in many current and future applications, in particular as functional blocks in electronics, batteries, catalysis, ultrahigh density data storage, and drug delivery. The text first discusses the methods used to produce nanostructures and then presents examples of various nanostructures. Describes various nanostructures that are little known in the scientific world. Offers a unifying vision of the synthesis of nanostructures and the generalization of rare nanoforms. Discusses current and future applications. Includes a CD-ROM with color versions of more than 100 nanostructures"-- Vydavatelská anotace
Keywords: nanomateriály; nanostructure materials; příručky; handbooks, manuals, etc